A study to assess efficacy of lower dose ketamine in labor analgesia and its effect on maternal and perinatal outcome - Singh, Kavita N.; Tamta, Nivedita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Present study is planned to study the effectiveness of lower dose ketamine in labor analgesia and its effect on progression of labor, maternal and perinatal outcome. Methods: After obtaining ethical approval from institutional ethical committee, a prospective randomized interventional case control study was conducted in Department of obstetrics and gynecology, N.S.C.B medical college, Jabalpur. Parturient in active labor without risk factors were given 0.2 mg/kg intravenous ketamine in bolus form and 0.1 mg/kg in maintenance dose at 30 minutes interval till full dilatation and the results were analyzed using VAS scale and WHO partogram. Results: In present study, 280 parturient were included in the study. In 140 cases, induction-delivery interval was shortened in 47.10% cases. Pain relief was satisfactory (VAS 2-8) in 77.90% cases. However, 80.70% cases had transient light headedness. Overall satisfaction was significantly high in the intervention group (P<0.001). Conclusions: A lower dose ketamine in bolus form with loading dose of 0.2 mg/kg followed by maintenance dose of 0.1 mg/kg could provide safe and acceptable analgesia during labor and delivery.